The Triticum Mosaic Virus 5’ Leader Binds to Both eIF4G and eIFiso4G for Translation - Roberts, Robyn; Mayberry, Laura K.; Browning, Karen S.; Rakotondrafara, Aurélie M. (PLOS ONE, 2017)
We recently identified a remarkably strong (739 nt-long) IRES-like element in the 5’ untranslated region (UTR) of Triticum mosaic virus (TriMV, Potyviridae). Here, we define the components of the cap-binding translation initiation complex that are required for TriMV translation. Using bio-layer interferometry and affinity capture of the native translation apparatus, we reveal that the viral translation element has a ten-fold greater affinity for the large subunit eIF4G/eIFiso4G than to the cap binding protein eIF4E/eIFiso4E. This data supports a translation mechanism that is largely dependent on eIF4G and its isoform. The binding of both scaffold isoforms requires an eight base-pair-long hairpin structure located 270 nucleotides upstream of the translation initiation site, which we have previously shown to be crucial for IRES activity. Despite a weak binding affinity to the mRNA, eIFiso4G alone or in combination with eIFiso4E supports TriMV translation in a cap-binding factor-depleted wheat germ extract. Notably, TriMV 5’ UTR-mediated translation is dependent upon eIF4A helicase activity, as the addition of the eIF4A inhibitor hippuristanol inhibits 5’ UTR-mediated translation. This inhibition is reversible with the addition of recombinant wheat eIF4A. These results and previous observations demonstrate a key role of eIF4G and eIF4A in this unique mechanism of cap-independent-translation. This work provides new insights into the lesser studied translation mechanisms of plant virus-mediated internal translation initiation.